A Prospective Study on Clinical Profile with Special Reference to Etiology, Management and Drug Utilisation Review on Cerebrovascular Accident with Ischemic and Hemorrhagic Stroke - Sayyed, Basheer; Shaik, Mohammad Akbar; Kamitkar, Sripriya; Shaik, Muazzamma; Nagarajan, Govindarajan (Indian Journal of Pharmacy Practice)
Background: Stroke is one of the leading causes of death and long-term disability in world. Stroke is an important cause of premature death and disability in low-income and middle-income countries like India, largely driven by demographic changes and enhanced by the increasing prevalence of key modifiable risk factors. Main aim of our study was to assess the clinical profile with special reference to the etiology of the condition, the management and drug utilization review. Methods: A Prospective observational study of 6 months was performed at general medicine department of the tertiary care government general hospital, Kurnool. Total of Hundred Patients aged above 20 years with Cerebrovascular accident with ischemic and hemorrhagic stroke were included following inclusion and exclusion criteria to observe their demographic profile and drug use. The data was analyzed summarized as frequency and percentage by using Microsoft Excel. Results: In our prospective study of hundred patients on cerebrovascular acccident with ischemic and hemorrhagic stroke. We observed males (70%) were more than females (30%). Stratification based on age showed patients admitting to general ward were frequently within the age group of 50-60 and 60-70. Among 100 patients studied, Hypertension (74%), Diabetes mellitus (23%), Smoking (34%) and alcohol (34%) were the risk factors respectively. Conclusion: We observed age, hypertension, diabetes mellitus, smoking and alcohol were the major risk factors. We conclude that proper risk factor management and following the guidelines in the treatment reduces the severity, thereby the prognostic factors will be good.
Keywords: Ischemic Stroke; Hemorrhagic Stroke; Precipitating Factors; WHO Prescribing Indicators; Drug Utilisation Review.